2021
DOI: 10.1007/s10980-021-01205-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-taxon conservation in northern forest hot-spots: the role of forest characteristics and spatial scales

Abstract: Context Biodiversity is highly affected by industrial forestry, which leads to the loss and fragmentation of natural habitats. To date, most conservation studies have evaluated associations among a single species group, forest type, or spatial scale. Objective The objective was to evaluate the richness of multiple species groups across various forest types and characteristics at multiple scales. Methods We used the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
1
4
1
Order By: Relevance
“…For example, the quality of deadwood as lichen habitat may be higher in old forests than elsewhere in the landscape. This is supported by a previous study by Kärvemo et al (2021), who also found that the amount of old forest, but not that of deadwood, in the landscape explained species richness of indicator lichens in WKHs. Deadwood quality in terms of e.g.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For example, the quality of deadwood as lichen habitat may be higher in old forests than elsewhere in the landscape. This is supported by a previous study by Kärvemo et al (2021), who also found that the amount of old forest, but not that of deadwood, in the landscape explained species richness of indicator lichens in WKHs. Deadwood quality in terms of e.g.…”
Section: Discussionsupporting
confidence: 87%
“…Old forests are regarded as an important habitat for various species groups, and the proportion of old forests in the landscape has previously been found to increase the species richness of deadwood‐dwelling beetles (e.g. Olsson et al, 2012) and indicator species of lichens, fungi and vascular plants (Kärvemo et al, 2021). The proportion of old forests explained lichen species density better than the proportion of protected forests, which suggests that there are old forests with high biodiversity values that remain outside protected areas in our study regions, or that protected areas include forests with lower biodiversity value, for example, former production stands or forests with lower productivity (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in deadwood availability and diversity due to forestry and other types of land use is the main explanation for loss of biodiversity on saproxylic species (Siitonen 2001 ; Stokland et al 2012 ; Löfroth et al 2023 ). Species richness and ecological communities of deadwood dependent species (insects, wood fungi, bryophytes and lichens, and indirectly also top predators such as woodpeckers) is determined by amount (abundance and volume) and diversity of deadwood in terms of tree species, trunk size, posture, mortality factor (e.g., wind, fire) and stage of decomposition (Siitonen 2001 ; Similä et al 2003 ; Junninen and Komonen 2011 ; Seibold et al 2016 ; Hägglund and Hjältén 2018 ; Kärvemo et al 2021 ). In general, high amounts of deadwood have shown to be good a proxy for biodiversity with 20 m 3 ha −1 serving as a threshold for maintaining high species richness of rare and red-listed saproxylic species, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity indices used were Shannon-Wiener index (H'), Gini-Simpson index (1-D), the effective number of species from H', community dominance index used Berger-Parker dominance, and Rényi entropy for relative measures of community diversity and evenness (Tóthmérész 1995;Jost 2006;Maurer and McGill 2010;Leinster and Cobbold 2012;Morris et al 2014;Mbenoun et al 2017;dos Santos et al 2020;Nur 'Aqilah et al 2020). Species accumulation curves were generated by collector and random methods with 1000 permutations (Schön et al 2018;Atrena et al 2020;Kärvemo et al 2021). The analysis of the macrofungal species distribution was done by Venn diagram (López-Quintero et al 2012;O'Hanlon et al 2013;Brunner et al 2014;Ghate et al 2014;Wei et al 2019;Ye et al 2019;Runnel et al 2021).…”
Section: Discussionmentioning
confidence: 99%